BATCH AND FLOW INJECTION SPECTROPHOTOMETRIC METHODSFOR DETERMINATION OF PARACETAMOL IN PHARMACEUTICALPREPARATIONS VIA OXIDATIVE COUPLING WITH4-AMINOANTIPYRINE - Al-Abachi, Mouayed Q; Sinan, Raghad; Falah, Zaineb (Al-Nahrain Journal of Science, 2010)
A simple, rapid and sensitive batch and flow injection spectrophotometric methods have been developed for the determination of paracetamol in pure form and pharmaceutical preparations. The proposed methods are based on the oxidative coupling reaction of paracetamol with 4-aminoantipyrine in presence of ammonium persulfate in alkaline medium to produce an orangereddish product that having absorptivity maximum at 461 nm. The optimum reaction conditions and other analytical parameters have been evaluated. Linearity was observed from 2-16 and 100-700 g mL -1 paracetamol by batch and flow injection procedures, respectively. Statistical analysis of the results and comparison with results by the British Pharmacopoeia method are also reported.